2022
DOI: 10.1038/s41598-022-07688-1
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of engaging in sports and exercise volunteering among older adults in Japan

Abstract: This study aimed to identify factors associated with engaging in sports and exercise volunteering among older adults. We used cross-sectional data from the Japan Gerontological Evaluation Study (JAGES), a nationwide mail survey of 20,877 older adults from 60 municipalities. Multilevel mixed-effects logistic regression analysis was used to investigate the correlation between engaging in sports and exercise volunteering and 39 variables classified into five factors: (1) demographic and biological, (2) behavioral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…Research has shown that participating in leisure activities can contribute to better physical health outcomes (1), such as improved mobility and reduced risk of chronic illnesses (3). It can also improve cognitive function (4), reduce feelings of social isolation and loneliness (5), and enhance overall mental health and well-being (6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has shown that participating in leisure activities can contribute to better physical health outcomes (1), such as improved mobility and reduced risk of chronic illnesses (3). It can also improve cognitive function (4), reduce feelings of social isolation and loneliness (5), and enhance overall mental health and well-being (6).…”
Section: Discussionmentioning
confidence: 99%
“…Leisure activity is a topic of growing interest in the literature, as it is increasingly recognized as an essential aspect of elderly well-being (1)(2)(3)(4). Engaging in leisure activities has been associated with a range of physical (5,6), cognitive (6), and social benefits (7,8), including improved mental health (7), reduced stress (8), and increased social relationships (5). Additionally, leisure activity has been shown to have a significant impact on the health status among the elderly, who may face a range of challenges related to aging, such as declining health, loss of social networks, and reduced mobility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is evident that the ndings of domestic and foreign scholars on this research topic are controversial. e most important feature of the retirement transition is the reduction or loss of occupational routines, income, social connections, and status, and this change in personal status may stimulate changes in behavior, which will influence healthy lifestyle choices [4]. Some scholars have found that retirement makes lifestyle changes such as socializing, sleeping, smoking, and drinking, which affect one's health level.…”
Section: Introductionmentioning
confidence: 99%